Logical derivation search with assumption traceability - Birštunas, Adomas; Reivytytė, Elena (Lietuvos matematikos rinkinys, 2021)
In this paper authors research the problem of traceability of assumptions in logical derivation. The essence of this task is to trace which assumptions from the available knowledge base of assumptions are necessary to derive a certain conclusion. The paper presents a new derivation procedure for propositional logic, which ensures traceability feature. For the derivable conclusion formula derivation procedure also returns the smallest set of assumptions those are enough to get derivation of the conclusion formula. Verification of the procedure were performed using authors implementation.
Keywords: propositional logic; traceability; loop checking